PENGARUH SIKAP DAN DEMOGRAFI KE ATAS PRODUKTIVITI KERJA PENSYARAH MUSLIM: KAJIAN DI UNIVERSITI MALAYA - Abdul Ghani Azmi, Ilhaamie (Jurnal Syariah, 2019)
Employees are one of the assets needed in order to produce work productivity. Therefore, attitudes and demographic details of an employee can produce behaviors which can influence work producitivity. This study aims to investigate the influence of attitudes and demographic details of permanent Muslim lecturers in Universiti Malaya to their work productivity. The total response is 102. It is found out that gender, age, marital status and tenure are related significantly with work productivity. Meanwhile, work involvement and relationship with Allah are related significantly with their work productivity